ANALISA HUKUM ORANG TUA YANG MENJADIKAN ANAK SEBAGAI MEDIA ENDORSEMENT SUATU PRODUK - Baskoro, Fajar Pandu; Ahmad, Gelar Ali (NOVUM : JURNAL HUKUM, 2018)
Endorsement is one of the communication and marketing strategies that is usually done through online shops to artists/celebrities on social media. Endorsement aims to create public interest in the products offered on social media. In the current reality, product endorsements often involve children in the communication process in delivering on social media as well as product photos and certain advertisements. Indirectly, the child has generated (financial) income from media endorsements. This leads to exploitation of children who are not realized by their parents because children's rights in accordance with the Child Protection Act are not properly accepted by children. This study aims to determine and analyze the actions of parents who make children as a media endorsement of a product, including acts of child exploitation and analyze the legal consequences of parents who make children as a media endorsement of a product. This study uses a normative legal research method with a statutory and conceptual approach. The legal materials used are primary legal materials and secondary legal materials obtained through literature study.